Pedestrian whole body ground contact mechanisms and head injury assessment following vehicle impact - SHANG, SHI (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2020)
According to the WHO, there are an estimated 1.35 million road-traffic related deaths each year, with pedestrians constituting approximately 22% of this figure, which justifies the necessity of research into vehicle-pedestrian collisions. Previous researchers have primarily focused on the injuries that pedestrians experience as a result of contact with the vehicle, however, ground related injuries and the mechanisms have been largely neglected. Accordingly, the purpose of this study is to significantly strengthen the understanding of pedestrian ground contact, to investigate what factors influence pedestrian ground contact injury severity, and to determine injury prevention strategies. An analysis of GIDAS vehicle-pedestrian crash data showed that head, thorax, and upper/lower extremities injuries are the most frequent pedestrian ground related injuries. The severity of ground related injuries is greatly affected by vehicle speed and pedestrian age. Older pedestrians are more at risk of suffering thorax injuries. Logistical analysis indicates that normalized bonnet leading edge height (NBLEH) is a predictor of the risk of AIS2 + ground related injuries. Prevention of all ground related pedestrian injuries for vehicle impact speeds below 40 km/h would bring very substantial injury cost reductions. An analysis of real-world vehicle-pedestrian collision videos from Youtube has been done in Chapter 5 to provide a basic understanding of pedestrian ground contact mechanism. The study consisted of 29 videos and examined the influencing factors that affect the mechanisms of pedestrian ground contact. It was observed that pedestrian projection increases with the vehicle speed, while smaller NBLEH resulted in larger pedestrian rotations, which indicates the potential effects that vehicle front shape has on the resulting pedestrian ground contact injuries. Six cadaver tests were conducted in LBA, IFSTTAR, Aix-Marseille University, France, which provided data relating to the pedestrian's kinematics during ground contact. It was observed that there is approximately 500ms of continued interaction between the pedestrian and the vehicle until separation occurs, which is followed by a flight period of around 200ms, finally terminating during ground contact. The linear accelerations in ground contact for vehicle impact speeds of 20 and 30 km/h are generally higher than the acceleration in the vehicle contact The predicted risk of rotationally induced brain injury caused by ground contact is high for the 20 km/h test, highlighting the risk of pedestrian injuries from ground contact even at very low speeds. Validation of both the MB and FE pedestrian models is yet to be completed in ground contact, therefore, a robust comparison of the pedestrian's motion in MADYMO environment with the pedestrian's motion in the cadaver test footage was conducted, thus revealing the competency of the MB model to predict the pedestrian's trajectory during a collision. It shows that contact characteristics of vehicle front-end greatly influence pedestrian post-impact kinematics and the induced injury predictions. In two of these reconstructed simulations, the MB pedestrian model bounded off the vehicle in a dissimilar motion to the motion observed in the staged tests. Although the pedestrian model failed to represent all the cadaver tests with exact kinematics, the model is partially suitable for use in a virtual test system (VTS) under low speed impact configurations. An inverse method based on a Virtual Test System (VTS) was used to correlate the distribution of impact parameters (vehicle speed, pedestrian height and pedestrian gait) with the predicted injuries, thus allowing the weighting of each parameter (Weighted Injury Costs) with its predicted injury to be determined. VTS showed that there was no significant difference in the WIC scores for the two shapes ('Good shape' and 'poor Shape') in each category of vehicle. Although for the van and SUV categories, the differences become significantly large under test samples of 120. The good shape vehicles are at least not worse in pedestrian-friendly than the poor shape vehicles. Together these studies provide significant new insights into pedestrian ground contact kinematics and injuries.
APPROVED
Keywords: Pedestrians, vehicle impact, ground contact, head injury, model assessment, cadaver impact tests